Marketing social responsibility - Sumitro Banerjee; Luc Wathieu (European School of Management and Technology (ESMT), 2013)
We analyze the marketing strategies of vertically differentiated firms when consumers observe their performance on corporate social responsibility (CSR) and firms simultaneously decide the price, advertising intensity and the investment in CSR. While advertising increases consumers' perception of product quality, CSR is introduced as an observable and measurable behavior or output which adds value for the society and exceeds levels set by obligatory regulation or standards enforced by law (Kitzmueller and Shimshack 2012). Results show that the firm strategies are contingent on product quality. A high quality monopolist charges a higher price, spends more on advertising but less on CSR to sell only to consumers who have a higher valuation of product quality. A low quality monopolist, in contrast, charges a lower price, spends less on advertising but more on CSR to address the entire market. However, in the presence of a high quality competitor, a low quality firm spends less on CSR than in a monopoly but may still spend more than the high quality competitor if the size of the low-end market is sufficiently large. Finally, when quality is not observable, a high quality firm spends more on CSR and charges a higher price to signal product quality. We conclude that CSR is a greater strategic consideration for firms who either rely on extensive market coverage or need to signal higher quality.
urn:nbn:de:101:1-2013071912595
Keywords: 650; Corporate social responsibility; vertical differentiation; signaling games; Corporate Social Responsibility; Marketingmanagement; Firmenimage; Konsumentenverhalten